Rapid assessment of insect pollination services to inform decision‐making - Fabrizia Ratto; Tom D. Breeze; Lorna J. Cole; Michael P. D. Garratt; David Kleijn; Bill Kunin; Denis Michez; Rory O'Connor; Jeff Ollerton; Robert J. Paxton; Guy M. Poppy; Simon G. Potts; et al. (Conservation Biology, 2022)
Pollinator declines have prompted efforts to assess how land‐use change affects insect pollinators and pollination services in agricultural landscapes. Yet many tools to measure insect pollination services require substantial landscape‐scale data and technical expertise. In expert workshops, 3 straightforward methods (desk‐based method, field survey, and empirical manipulation with exclusion experiments) for rapid insect pollination assessment at site scale were developed to provide an adaptable framework that is accessible to nonspecialist with limited resources. These methods were designed for TESSA (Toolkit for Ecosystem Service Site‐Based Assessment) and allow comparative assessment of pollination services at a site of conservation interest and in its most plausible alternative state (e.g., converted to agricultural land). We applied the methods at a nature reserve in the United Kingdom to estimate the value of insect pollination services provided by the reserve. The economic value of pollination services provided by the reserve ranged from US$6163 to US$11,546/year. The conversion of the reserve to arable land would provide no insect pollination services and a net annual benefit from insect‐pollinated crop production of approximately $1542/year (US$24∙ha –1 ∙year –1 ). The methods had wide applicability and were readily adapted to different insect‐pollinated crops: rape ( Brassica napus ) and beans ( Vicia faba ) crops. All methods were rapidly employed under a low budget. The relatively less robust methods that required fewer resources yielded higher estimates of annual insect pollination benefit.